Effect of Moisture Content and Grain Variety on Frictional Properties and Specific Heat Capacity of Acha (Fonio) Grains - Kawuyo, U. A.; Aviara, N. A.; Okolo, D. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
There are many varieties of acha, but the most prominent two are white acha (Digitaria exilis) and brown acha (Digitaria iburua). This study was undertaken to determine the static coefficient of friction, kinetic coefficient of friction and specific heat of the grains as influenced by moisture content. The moisture levels considered were 5, 11, 23 and 28% db for the white variety and 5, 9, 21 and 30% db. The study revealed that increase in moisture content resulted to increase in the value of the properties considered for both varieties, with the white acha showing the highest values. Static coefficient of friction increased linearly with moisture content and had maximum values of 0.49 - 0.62 for the brown variety and 0.52-0.66 for the white variety all on steel sheet, while the minimum values for both varieties were on glass surface. Kinetic coefficient of friction increased linearly with moisture content and the highest value was obtained on hessian bag material (0.62-0.66) with the least being on steel sheet (0.58-0.64) for the two acha grain varieties. The study further revealed that, specific heat capacity of acha grains increased with increase in moisture content from 2.93 – 11.29 kJ/kgK (5 – 28% db) for the white variety and from 2.33 – 13.88 kJ/kgK (5 – 30% db) for brown variety. This study concludes that variety and changes in moisture content significantly affected the determined properties of acha.